A study of satisfaction with research capacity development of Master of Public Health and its influencing factors - Bin Hu; Haitao Zhou; Yue Wang; Li Zheng; Min Li (Frontiers Media S.A., 2023)
ObjectiveTo understand the satisfaction and the current status of the training of scientific research ability of Master of Public Health students in universities, analyze the influencing factors and explore their solutions, in order to provide reference for improving the scientific research ability of Master of Public Health students.MethodsA questionnaire was used to survey Master of Public Health students in nine universities. The data were analyzed by descriptive statistics and multifactor logistic regression.ResultsThe overall satisfaction self-rating score for research capacity of Master of Public Health students was (3.29 ± 0.87), with the highest score for mentor exchange (3.78 ± 0.81) and the lowest score for subsidized treatment (1.86 ± 0.96). Satisfaction with the practice unit and school dimensions was significantly lower than the mentor dimension. The length of practice in the practice unit, subsidy treatment, importance of research capacity development, development tendency, and current status of research were influential factors contributing to the difference in satisfaction with research capacity development of Master of Public Health students (P < 0.05).ConclusionThe overall scientific training quality of Master of Public Health students is high, but there are still many aspects that need to be solved. Colleges and universities should join the funding system adapted to the practice process of Master of Public Health students and guarantee the construction of the system of student subsidy treatment. Secondly, they should strengthen the construction of public health supervisory team and improve the frequency and quality of scientific research exchanges between teachers and students. In addition, colleges and universities should improve the existing research incentives and policies, and adopt multiple forms and types of research incentives. Finally, colleges and universities should improve the research training system and the construction of research resources for Master of Public Health.